Social self, family, and social attitudes during the period of the Covid-19 pandemic constraints in 2020 - Chtouris, Sotiris; Zissi, Anastasia (The Greek Review of Social Research, 2020)
The current pandemic Covid-19 health crisis is both the beginning and the result of a parallel social and economic crisis. In this dynamic field, social management requires resilient social institutions and a social self coping with the main negative effects of the pandemic namely social atrophy and social implosion in a creative and innovative way. Studying the social self and its recovery methods from social trauma resulting from the current Covid-19 pandemic requires understanding crucial social self dimensions and functions not only in the present crisis of social implosion but also in the precursor state in which the modern social self is characterized by an explosion of dense with strong intensity of networks of communication, economic exchange and every day social life. The purpose of this text is to provide a research plan and research data for a method of reflection and resilience of our social self in the current conditions of strong social distance, self-restraint and disconnection from the economy. This article concludes with suggestions for a Clinical Sociology Implementation of a protocol ensuring the resilience of individuals and communities s that have suffered under the Covid-19 pandemic and some suggestions for an individual and collective strategy.